THE DEVELOPMENT OF ELECTRONIC LIBRARY IN THE NATIONAL AVIATION UNIVERSITY - Іванкевич, О. В.; Вахнован, В. Ю. (Proceedings of National Aviation University, 2012)
The Information technologies, implemented and used for today in the scientific and technical library of the National aviation university are considered. In this article introduced the stages of work on creation of the new systems of access to the existing electronic resources, creation of general and bibliographic electronic catalogues, and also libraries of electronic information resources. The necessity in usage of the RFID technologies with the purpose of safety and effective exploitation of library’s funds is grounded